Industrial Hemp Logistics in Poland from the Perspective of a Research Institute - Roman DOMANSKI; Magdalena MISIAK (Communications of International Proceedings, 2021)
Current interest in industrial hemp focuses mainly on agricultural, biological and chemical issues. Yet, industrial hemp logistics is still a bit of a mystery. The authors of the article try to answer the following research question: how are the logistics processes of industrial hemp implemented? The aim of the article is to expand scientific and business knowledge in the area of industrial hemp logistics in theoretical (cognitive) and practical (exploratory) dimensions. In the theoretical part, a systematic literature review about industrial hemp based on the Scopus database was done. In the practical part, a case study analysis by the Institute of Natural Fibers and Medicinal Plants (INF&MP) was carried out – a location and economic analyses. Analysis of the literature in the Scopus database shows that there are not many publications on strictly industrial hemp logistics (only 5), and those that are available contain quite general descriptions. Analysis of the case study shows that although the INF&MP controls only 20% of the Polish industrial hemp market, its offer is the widest (5 out of 7 varieties). The market value of the INF&MP industrial hemp varieties at the raw material purchase price is PLN 7.425 million. The further development of industrial hemp will be stimulated on the one hand by new applications (demand), and on the other hand by economic benefits obtainable from growing it (supply). In the longer term, wider availability and disclosure of information regarding industrial hemp logistics is expected.
Keywords: Logistics; industrial hemp; economic analysis; location analysis; legal regulations; systematic literature review; the Institute of Natural Fibers and Medicinal Plants (INF&MP).